Is asymptomatic bacteriuria associated with short cervical length in women with a singleton pregnancy, a secondary analysis of two national cohort studies with small embedded randomized controlled trials. (May 2020) - Koningstein, Fiona N.; Schneeberger, Caroline; van der Ven, A. Jeanine; van Os, Melanie A.; Pajkrt, Eva; de Groot, Christianne J.M.; Mol, Ben Willem J.; Geerlings, Susanne E.; Kazemier, Brenda M.
Abstract: Objective: To assess the association between asymptomatic bacteriuria (ASB) and short cervical length (CL), since they are both associated with preterm delivery. Study design: In two prospective multicentre cohort studies, pregnant women were screened for the presence of ASB and short CL (≤25 mm). We compared CL in women with and without ASB. Both studies had a small randomised clinical trial embedded. Results: Our study population comprised 1 610 women, of whom 114 were ASB positive. Median cervical length was similar in women with and without ASB (44.0 vs 44.0 mm, P = 0.60). More women in the ASB positive group had a short CL compared to the ASB negative group (1.8 % versus 0.4 %, P = 0.047)). The gestational age at delivery did not differ between the groups (ranging from 38 + 3 in women with ASB and short CL to 39 + 5 in women without ASB with a short CL P = 0.52). No preterm births occurred in women with a short cervical length (regardless of ASB status). In the women without ASB and no short CL 4.8 % had a preterm birth, in the women with ASB but not a short CL 4.1 % had a preterm birth. Conclusion: While ASB status did not influence median cervical length, we found a significant relationship between a short CL and ASB positive women. We found no statistical significant difference on the preterm birth rate and mean gestational age.